INSIGHTS FROM ACADEMIC TRIP: A SCOPUS-AI REVIEW ON BUMIPUTERA ENTREPRENEURSHIP CHALLENGES - Mat Khairi, Siti Murni; Rozali, Norhasyikin; Shaharuddin, Sharifah Syakila Syed; Salleh, Shazwani Mohd; Hamzah, Sharifah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Bumiputera entrepreneurship is a cornerstone of Malaysia’s economic development, yet Bumiputera entrepreneurs face persistent challenges that hinder their ability to thrive in competitive markets. Key issues include limited access to funding, inadequate business skills, cultural barriers, and low levels of technological adoption, which collectively restrict their capacity to scale operations and compete effectively. To address these concerns, this study aims to provide a comprehensive understanding of the challenges faced by Bumiputera entrepreneurs by using a Scopus-AI-driven systematic review from 2010 to 2025, with experiential learning opportunities gained through academic trips. This study also synthesizes findings through concept mapping. The main findings highlight Bumiputera entrepreneurship challenges include market access and competition, human capital issues, financial constraints, cultural and social factors. Insights from academic trips further enrich the findings and reveal that experiential learning opportunities, such as academic trips, play a transformative role in bridging the gap between theoretical knowledge and practical application. By integrating classroom learning with real-world exposure, participants gain actionable insights into overcoming challenges and developing critical skills. This study emphasizes on the importance of collaboration among stakeholders, including policymakers, educators, and industry leaders, to design inclusive support mechanisms and scalable solutions. The implications of this research extend to fostering inclusive economic growth by empowering Bumiputera entrepreneurs to overcome the entrepreneurship challenges and contribute meaningfully to Malaysia’s development agenda. Future research should explore cross-disciplinary approaches and evaluate the effectiveness of innovative policies aimed at addressing these challenges.